Sociological Elements in Economic Thought: II. The Analytical Factor View^1 - Parsons, Talcott (Quarterly Journal of Economics, 1935)
I. The analytical factor view of economics. Non-economic sociological supplements (a) Durkheim, 647.— (b) Pareto, 650.— (c) Max Weber, 654. — II. General methodological considerations: empiricism, economics and sociology, 657.